Susceptibility of Multiple Primary Cancers in Patients With Head and Neck Cancer: Nature or Nurture? - Zhang, Wei-long; Zhu, Zhuo-li; Huang, Mei-chang; Tang, Ya-Jie; Tang, Ya-ling; Liang, Xin-hua (Frontiers in Oncology, 2019)
Multiple primary cancers (MPCs) are major obstacles to long-term survival in head and neck cancer (HNSCC), however, the molecular mechanism underlying multiple carcinogenesis remains unclear. “Field cancerization” is a classical theory to elaborate the malignant progression of MPCs. Apart from environmental and immune factors, genetic factors may have great potential as molecular markers for MPCs risk prediction. This review focuses on inherited and acquired gene mutations in MPCs, including germ-line mutation, single-nucleotide polymorphism, chromosomal instability, microsatellite instability and DNA methylation. And definition and prognosis of MPCs have also been discussed. These may pave the way for the early detection, prevention and effective treatment of MPCs in HNSCC.